2001
DOI: 10.1007/s004390100474
|View full text |Cite
|
Sign up to set email alerts
|

Carrier rate of APC I1307K is not increased in inflammatory bowel disease patients of Ashkenazi Jewish origin

Abstract: Colorectal cancer (CRC) occurs with an increased incidence in individuals with chronic inflammatory bowel disease (IBD) of the colon. Recent data suggest that a family history of colorectal cancer is an independent risk factor for CRC in IBD, an observation that implies that genetic factors are relevant to the development of CRC in this context. Among the genetic defects associated with CRC, the APC I1307K mutation has been detected nearly exclusively in individuals of Ashkenazi Jewish (AJ) origin, occurring i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
(40 reference statements)
1
4
0
Order By: Relevance
“…Studies from various communities worldwide in which Ashkenazi Jews are concentrated have examined the occurrence of this genetic variant in Jewish Ashkenazi patients with breast carcinoma, ovarian carcinoma, and ulcerative colitis, because these diseases are more common in the Jewish people. 3, 19–24 Overall, no such associations with the I1307K variant were found other than a significant excess risk (OR, 1.5) in BRCA1 or BRCA2 breast carcinoma heterozygotes, a finding that the authors also felt did not justify clinical testing for I1307K 20. Our clinical findings are consistent with the characteristics of many other Ashkenazi Jewish diseases, which are mostly autosomal‐recessive disorders,25 for example, Gaucher disease, in which the asymptomatic heterozygous carrier rate in Ashkenazi Jews is 5.8%, but only a minority (10.3%) of homozygotes are actually symptomatic.…”
Section: Discussionsupporting
confidence: 77%
“…Studies from various communities worldwide in which Ashkenazi Jews are concentrated have examined the occurrence of this genetic variant in Jewish Ashkenazi patients with breast carcinoma, ovarian carcinoma, and ulcerative colitis, because these diseases are more common in the Jewish people. 3, 19–24 Overall, no such associations with the I1307K variant were found other than a significant excess risk (OR, 1.5) in BRCA1 or BRCA2 breast carcinoma heterozygotes, a finding that the authors also felt did not justify clinical testing for I1307K 20. Our clinical findings are consistent with the characteristics of many other Ashkenazi Jewish diseases, which are mostly autosomal‐recessive disorders,25 for example, Gaucher disease, in which the asymptomatic heterozygous carrier rate in Ashkenazi Jews is 5.8%, but only a minority (10.3%) of homozygotes are actually symptomatic.…”
Section: Discussionsupporting
confidence: 77%
“…Ashkenazi Jews have an increased incidence of inflammatory bowel disease [22] affecting the large bowel, a known risk factor for developing colorectal cancer. In a study of 306 Ashkenazim with IBD, there was no difference in their carrier rate of the I1307K polymorphism (6.9%) compared to 308 of their unaffected relatives (6.2%) [23]. The incidence of I1307K in both is similar to that reported for the general Ashkenazi population [15,[24][25][26][27][28][29].…”
Section: Apc*i1307kmentioning
confidence: 74%
“…1 Several studies have confirmed that the magnitude of risk of colorectal cancer conferred by this polymorphism is approximately 1.8 times the risk among noncarriers. [2][3][4][5][6][7][8] Some have looked at this polymorphism with regard to other disease groups such as inflammatory bowel disease 9 and multiple adenomas. 10-11 APC I1307K does not account for the increased risk of colorectal cancer in patients with inflammatory bowel disease, but it appears to be overrepresented among individuals with multiple adenomas.…”
mentioning
confidence: 99%